2022
DOI: 10.3389/fpsyt.2022.1019367
|View full text |Cite
|
Sign up to set email alerts
|

Potential value of serum brain-derived neurotrophic factor, vascular endothelial growth factor, and S100B for identifying major depressive disorder in knee osteoarthritis patients

Abstract: BackgroundThe chronic pain and functional limitations in osteoarthritis (OA) patients can increase risk of psychiatric disorders, e.g., major depression disorder (MDD), which may further aggravate the clinical symptoms of OA. Early detection of MDD is essential in the clinical practice of OA.Materials and methodsTwo hundred and fifteen participants with knee OA were recruited, including 134 MDD patients (i.e., MDD group) and 81 ones without MDD (i.e., control group). Among them, 81 OA participants in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“… 55 VEGF is thought to have antidepressant-like effects, and VEGF signalling mediates cell proliferation of antidepressants through Flk-1 and causes behavioural changes in chronic antidepressant models. 56 Warner-Schmidt reported that in a rat model of depression, VEGF expression in the hippocampus was elevated and was regulated by selective serotonin reuptake inhibitors or selective serotonin/norepinephrine reuptake inhibitors, which were used for antidepressant treatment. 57 EGF promotes the growth and development of the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“… 55 VEGF is thought to have antidepressant-like effects, and VEGF signalling mediates cell proliferation of antidepressants through Flk-1 and causes behavioural changes in chronic antidepressant models. 56 Warner-Schmidt reported that in a rat model of depression, VEGF expression in the hippocampus was elevated and was regulated by selective serotonin reuptake inhibitors or selective serotonin/norepinephrine reuptake inhibitors, which were used for antidepressant treatment. 57 EGF promotes the growth and development of the nervous system.…”
Section: Discussionmentioning
confidence: 99%